Developing Problem-Solving Based E-Student Liveworksheet to Improve Students’ Critical Thinking in Acid-Base - Mutiara, Fadilah; Azizah, Utiya; Ramadhania, Nurina Rizka (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study is conducted in response to the low levels of students’ critical thinking skills, particularly in interpretation, analysis, inference, and explanation, in the context of acid-base chemistry, as well as the scarcity of digital resources that promote active learning. The objective is to develop a problem-solving-based E-Student Liveworksheet to improve critical thinking skills related to acid-base material. Research and Development (R&D) was employed, following the 4D model (Define, Design, Develop, and Disseminate). The feasibility of the developed worksheet was evaluated using Nieveen’s criteria: validity, practicality, and effectiveness. Data were gathered through expert validation forms, student questionnaires, classroom observations, and critical thinking tests. The study involved eleventh-grade students at Gedangan Senior High School. Validation results showed a mode score of 4, indicating high content validity. The practicality score from student responses reached 95%, categorized as